Exosomal miR-6126 as a novel therapeutic target for overcoming resistance of anti-cancer effect in hepatocellular carcinoma - Hyemin Hwang; Jimin Kim; Tae-Hun Kim; Yeonju Han; Dayoung Choi; Sua Cho; Seunghwan Kim; Sanghee Park; Taehyun Park; Filippo Piccinini; Won Jong Rhee; Jae-Chul Pyun; et al. (BMC Cancer)
Abstract Background Hepatocellular carcinoma (HCC) stands as the sixth most prevalent cancer globally, presenting a substantial health challenge, particularly due to late-stage diagnoses that limit treatment effectiveness. Sorafenib, a multi-kinase inhibitor, is the primary chemotherapeutic agent for advanced HCC, but it only extends survival by 2–3 months. However, drug resistance remains a major clinical challenge, necessitating the exploration of new molecular mechanisms, including the role of microRNAs (miRNAs) in sorafenib resistance. In this study, we aimed to identify miRNAs within exosomes derived from sorafenib-resistant HCC cells to elucidate the molecular mechanisms underlying resistance. Methods Sorafenib-resistant cells were generated by culturing the human HCC cell line Huh7 in a medium containing 20 µM sorafenib for six months. Exosomes were isolated from the conditioned medium 24 h before cell harvest using exosome-depleted serum medium. miRNA sequencing and western blotting were used to analyze the expression profiles of exosomal miRNAs and proteins, respectively. pH measurement was performed to assess pH changes in response to sorafenib treatment and miRNA modulation. Results A total of 180 exosomal miRNAs were found to be dysregulated between sorafenib-treated control Huh7 (Huh7S) and sorafenib-resistant Huh7 (Huh7RS) cells, as well as between untreated control Huh7 and Huh7RS cells. Among these, miR-6126 was significantly downregulated in Huh7RS cells compared to Huh7S cells. Functional studies using 2-dimensional (D) and 3D cell culture systems revealed that miR-6126 overexpression reduced sorafenib resistance in Huh7RS cells, while its inhibition increased resistance in Huh7 cells. miR-6126 downregulated key proteins involved in cancer stem cell maintenance, such as CD44 and HK2. Furthermore, the pH level was elevated in cells overexpressing miR-6126 following sorafenib treatment, whereas inhibiting miR-6126 resulted in a lower pH. Conclusions Exosomal miR-6126 plays a pivotal role in sorafenib resistance and tumorigenesis, highlighting its potential as a novel therapeutic target for overcoming drug resistance in HCC.